2015
DOI: 10.17795/jhealthscope-30782
|View full text |Cite
|
Sign up to set email alerts
|

Seatbelt Use and Related Factors Among Drivers Involved in Road Crashes in Southeast Iran

Abstract: Background: Seatbelts are a relatively low-cost safety device that provides easy basic protection for occupants of 4-wheeled vehicles. Objectives: This study investigates frequency of seatbelt use and its related factors among drivers involved in a vehicle crash. Materials and Methods:In this cross-sectional study, all crash profiles recorded in a province from March 2010 to March 2011 were reviewed. Necessary information was extracted from crash reports in which at least one 4-wheeled vehicle was involved. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The findings of this study suggest an inverse relationship between seatbelt use and death in car occupants. The same result has also been reported by many earlier studies [22][23][24]. It has been demonstrated that fastening the seatbelt would reduce 40% to 50% of death cases in front seat occupants as well as 25% in rear occupants [25].…”
Section: Discussionsupporting
confidence: 84%
“…The findings of this study suggest an inverse relationship between seatbelt use and death in car occupants. The same result has also been reported by many earlier studies [22][23][24]. It has been demonstrated that fastening the seatbelt would reduce 40% to 50% of death cases in front seat occupants as well as 25% in rear occupants [25].…”
Section: Discussionsupporting
confidence: 84%
“…Several factors have been found to increase seat belt use, such as being in a city far from the capital, being female, driving a taxi [15], older age [10], and being more educated [7,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of those studies were conducted using secondary databases [8,10,12,13], through observations from outside the vehicles [7,[15][16][17] or through self-reports by the drivers [9,11,12,14]. Therefore, it is necessary to conduct field research that directly observes their use and the most important influences, especially in low-and middle-income countries such as Peru [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations